2017
DOI: 10.1177/2050312117743674
|View full text |Cite
|
Sign up to set email alerts
|

Physical condition, nutritional status, fatigue, and quality of life in oncological out-patients

Abstract: Objective:Early detection of limited physical activity and nutritional deficiencies in cancer survivors could contribute to early treatment and preservation of quality of life. The aim of this study is to describe the association of physical condition and nutritional status with fatigue and quality of life in oncological out-patients.Methods:Data in this descriptive study was collected on bioelectrical impedance analysis, postural stability (stability index), body mass index, Karnofsky Index, quality of life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…Participants of group G2 seem to have superior cell quantity, quality, and vitality, expressed by the strong correlation between PhA and BCM (r=0.732; p=0.007). Other studies have confirmed this finding, suggesting that PhA can be used as a predictor of cell quality and quantity of ICW [51]. Reductions in PhA may be explained by the reduction in fat-free mass and the increase in ECW, which expresses the state of cell hydration and the integrity of the cell wall [52].…”
Section: Discussionmentioning
confidence: 61%
“…Participants of group G2 seem to have superior cell quantity, quality, and vitality, expressed by the strong correlation between PhA and BCM (r=0.732; p=0.007). Other studies have confirmed this finding, suggesting that PhA can be used as a predictor of cell quality and quantity of ICW [51]. Reductions in PhA may be explained by the reduction in fat-free mass and the increase in ECW, which expresses the state of cell hydration and the integrity of the cell wall [52].…”
Section: Discussionmentioning
confidence: 61%
“…Fatigue can occur as an acute or chronic state, most often observed in specific medical disorders such as cancer, heart failure, and stroke [30,31]. Impaired nutritional status has frequently been linked to fatigue in cancer patients [32,33]. Stobäus et al moreover showed that recent protein intake in cancer patients is associated with higher fatigue, implying that not only nutritional status but also acute dietary intake has an effect on fatigue [34].…”
Section: Discussionmentioning
confidence: 99%
“…ESPEN strongly recommended PhA as a prognostic nutritional measure [24, 25]. The possibility of predicting the occurrence or exacerbation of a given disease is emphasized by many researchers around the world [8, 9, 26, 27]. Hui et al in their research phase angle retained its prognostic significance in the context of many known prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Low phase angle score is considered as an indicator of impaired cellular membrane integrity and also indicates the shift of body water from intracellular to extracellular compartments [7]. PhA is an important prognostic factor in numerous disease entities [8, 9]. The European Society for Clinical Nutrition and Metabolism (ESPEN) recommends the assessment of PhA as a prognostic measure of nutrition and a reliable prognostic marker.…”
Section: Introductionmentioning
confidence: 99%